Supporting the essential - Recommendations for the development of accessible and interoperable marine biological data products. (July 2020) - Lear, D.; Herman, P.; Van Hoey, G.; Schepers, L.; Tonné, N.; Lipizer, M.; Muller-Karger, F.E.; Appeltans, W.; Kissling, W.D.; Holdsworth, N.; Edwards, M.; Pecceu, E.; et al.
Abstract: In this paper we outline the stakeholder-led approaches in the development of biological data products to support effective conservation, management and policy development. The requirements of a broad range of stakeholders and iterative, structured processes framed the development of tools, models and maps that support the FAIR (Findable, Accessible, Interoperable, Reusable) data principles. By structuring the resultant data products around the emerging biological Essential Ocean Variables, and through the engagement with a broad range of end-users, the EMODnet (European Marine Observation and Data Network) Biology project has delivered a suite of demonstration data products. These products are presented in the European Atlas of Marine Life, an online resource demonstrating the value of open marine biodiversity data and help to answer fundamental and policy-driven questions related to managing the natural and anthropogenic impacts in European waters.